IMPROVEMENT OF QUALITY OF LIFE AS THE MAIN OBJECTIVE OF ALLERGIC RHINITIS THERAPY IN CHILDREN - R.T. Saygitov (Вопросы современной педиатрии, 2008)
Traditionally, efficacy of treating allergic rhinitis (AR) in children is evaluated on the basis of subjective and objective criteria connected with the more or less express character of symptoms. At the same time, there are all reasons to say that the evaluation of the quality of life (QOL) of a child more fully reflects his health than sole consideration of AR symptoms. As a result, the change of QOL in the course of treating AR may more precisely reflect the efficacy of illness treatment. This is especially noticeable when analyzing the results of treatment with the use of sedative antihistamine drugs, which arrest AR symptoms but exert a negative influence over the QOL indicators, such as activity, learning ability, social adaptation. New generation antihistamine drugs and intranasal corticosteroids do not have such influence over children's QOL. moreover, their regular use may help in decreasing the risk of development bronchial asthma and atopic dermatitis in children, which is another objective of AR therapy.Key words: children, quality of life, allergic rhinitis, treatment.